Co-Creation of Collective Values: Nurturing Thriving Rural Entrepreneurship - Asmit, Brilliant; Simatupang, Togar Mangihut; Rudito, Bambang; Novani, Santi (School of Business, IPB University (SB-IPB), 2024)
Background: Collaboration plays a very important role in fostering a thriving entrepreneurial ecosystem, unlike rural areas, which have constraints compared to urban areas and require special efforts to accelerate their economies.Purpose: This paper aims to explore how actors collaborate to create a prosperous entrepreneurial ecosystem in rural areas.Design/methodology/approach: We conducted a case study of Koto Mesjid Village, Indonesia, which involved collaboration between academics, government, business, and the community. Our research method involved content analysis of recorded academic reports regarding the case, using a systematic coding technique based on fundamental categories identified through a proposed model. The aim is to elucidate the relational dynamics among the ecosystem's actors, values, co-creation, and objectives.Findings/result: Our findings highlight the exchange of resources between the actors produced value that reformed the condition of rural entrepreneurial ecosystem. Collaboration led to densification and diversification of the ecosystem's resources, which in turn allowed its actors to discover new opportunities and increase their success in exploiting them. Conclusion: Building networks has the critical role to exchange knowledge in nurturing rural entrepreneurship. Policy makers can facilitate such networks to develop villages and promote regional economic growth.Originality/value: This study contributes to the conversation of service-dominant logic in the regional economic context by demonstrating that the co-creation of collective values is achievable and crucial for developing a thriving rural entrepreneurial ecosystem. Keywords: entrepreneurial ecosystem, service-dominant logic, value co-creation, regional development, rural